Transient receptor potential vanilloid 2-mediated shear-stress responses in C2C12 myoblasts are regulated by serum and extracellular matrix - Kurth, Felix (FEDERATION AMER SOC EXP BIOL, 2020)
10.1096/fj.15-275396